1991
DOI: 10.1002/1097-4679(199107)47:4<537::aid-jclp2270470411>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the mini-mental state exam in neurologically intact elderly

Abstract: Reliability and validity of MMSE were explored in a sample of 122 healthy, community‐residing elderly volunteers between the ages of 57 and 85, who were tested with a battery of neuropsychological tests over three annual probes. Test‐retest reliability ranged between .45 and 50 over a 1‐year interval and was .38 over a 2‐year period. Change on the MMSE of more than 5 points over a 2‐year period was associated with a neurological disorder. Significant correlations were found with many neuropsychological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
7

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 20 publications
3
45
1
7
Order By: Relevance
“…Non-population based MMSE change scores have been published 17 18. One study included individuals with progression to dementia and found “that changes of 3–5 points might be associated with change in affective state and psychological conditions at the time of testing” 17.…”
Section: Discussionmentioning
confidence: 99%
“…Non-population based MMSE change scores have been published 17 18. One study included individuals with progression to dementia and found “that changes of 3–5 points might be associated with change in affective state and psychological conditions at the time of testing” 17.…”
Section: Discussionmentioning
confidence: 99%
“…Because the MMSE was developed as a screen, a low score (less than 24/30) indicates both the possibility of cognitive impairment and the need for further evaluation. Test-retest reliability in neurologically healthy adults ranged between .45 and .50 over a one-year interval and .38 over a two-year period ( Mitrushina & Satz, 1991 ).…”
Section: Methodsmentioning
confidence: 99%
“…32 It evaluates most of the main domains of cognitive status and has been extensively validated. [31][32][33][34][35][36] We used the recommended cut-point score of ,24 points out of the total possible 30 points to indicate cognitive impairment. 37 …”
Section: Measurement Of Copd Severitymentioning
confidence: 99%